On generalized exponential chain ratio estimators under stratified two-phase random sampling. Issue 6 (19th March 2017) - Shabbir, Javid; Gupta, Sat
ABSTRACT: Sanaullah et al. (2014 ) have suggested generalized exponential chain ratio estimators under stratified two-phase sampling scheme for estimating the finite population mean. However, the bias and mean square error (MSE) expressions presented in that work need some corrections, and consequently the study based on efficiency comparison also requires corrections. In this article, we revisit Sanaullah et al. (2014 ) estimator and provide the correct bias and MSE expressions of their estimator. We also propose an estimator which is more efficient than several competing estimators including the classes of estimators in Sanaullah et al. (2014 ). Three real datasets are used for efficiency comparisons.